Targeted lipidomics meets transcriptomics: how cinobufagin rewires fatty acid, sphingolipid, and glycerophospholipid metabolism to combat hepatoma cell growth - Shao, Wanjun; Yu, Congying; Xu, Rufei; Rong, Xiaoqian; Yang, Ailin (Frontiers in Pharmacology, 2026)
IntroductionHepatocellular carcinoma (HCC) is a common malignant tumor, is characterized by an early stage that is not easy to diagnose and a high mortality rate in the late stage, which is a serious threat to patients' lives. Abnormalities in lipid metabolism are closely related to the development of HCC. Integrating transcriptomics and metabolomics analyses can help in the study of drug mechanism of action. Cinobufagin, is the main active ingredient for chinese medicine Chansu to exert anti-tumor effects, but the effects of cinobufagin on abnormal lipid metabolism in tumor cells are not clear.MethodsWe employed targeted lipid metabolomics to profile alterations in key lipid classes. Furthermore, integrated transcriptomics and metabolomics analyses were conducted to identify critical pathways involved in cinobufagin's action.ResultsIn this study, we demonstrate through the results of targeted lipid metabolomics that cinobufagin interferes with fatty acyls, sphingolipids, glycerophospholipids, glycerolipids, saccharolipids, and sterol lipids. The results of integration of transcriptomics and metabolomics identified that intervention in fatty acid metabolism (including biosynthesis of unsaturated fatty acids, fatty acid biosynthesis, fatty acid degradation, and fatty acid elongation), sphingolipid metabolism (including sphingolipid metabolism, glycosphingolipid biosynthesis-globo and isoglobo series, glycosphingolipid biosynthesis-lacto and neolacto series, glycosphingolipid biosynthesis-ganglio series), and glycerophospholipid metabolism (including glycerophospholipid metabolism, ether lipid metabolism, glycosylphosphatidylinositol (GPI)-anchor biosynthesis) may be partially responsible for the effect of anti-hepatoma cell growth induced by cinobufagin.DiscussionOur findings demonstrate that cinobufagin exerts anti-HCC activity partially through lipid metabolism, particularly by targeting fatty acid, sphingolipid, and glycerophospholipid pathways. This study is of great significance for the application of cinobufagin and chansu in clinical HCC treatment and promotes the development of new drugs from traditional Chinese medicine in the field of antitumor.